Dampak Positif dan Negatif Penggunaan Smartphone Terhadap Prestasi Belajar Siswa - Nurhalifah; Dedi Riyan Rizaldi; Muktofan; Nilwan; Ziadatul Fatimah (Action Research Journal, 2024)
Smartphones are handheld communication devices that have various capabilities and functions similar to computers and are not only used for SMS and telephone calls. Smartphones can store various kinds of data, operate applications that users want, and serve as a means of entertainment. This research aims to find out the positive and negative impacts of using smartphones on the learning achievement of class X Religion MA Plus Nurul Islam Sekarbela students. This research uses a descriptive-qualitative approach. Data collection techniques in this research are observation, interviews, and documentation. The subjects used in this research were four people. The results of this research show that smartphones have an impact on student learning achievement. Two students use smartphones to broaden their horizons and search for information related to learning; this improves their learning achievement. Meanwhile, the other two students mostly used smartphones to play games, so they forgot to spend time studying, causing their learning achievement to decline.